OC-117 Neoadjuvant precision chemoembolisation for easily resectable colorectal liver metastases. (28th May 2012) - Jones, R; Dunne, D; Fenwick, S W; Sutton, P; Malik, H; Poston, G
Abstract : Introduction: Peri-operative chemotherapy confers a 3-year progression free survival advantage for patients with colorectal liver metastases. Degree of post-chemotherapy tumour necrosis is associated with disease free survival. However, systemic neoadjuvant chemotherapy is associated with pathological damage to hepatic parenchyma, increasing perioperative morbidity and mortality. Irinotecan eluting beads (DEBIRI-TACE) are delivered to tumour intra-arterially, where they provide controlled & sustained delivery of Irinotecan directly to tumour, maximising response and reducing systemic exposure. This study aimed to examine the feasibility and safety of a single neoadjuvant bead embolisation 1-month before hepatectomy. Methods: Patients with easily resectable colorectal liver metastases received DEBIRI-TACE 1 month before surgery. Primary end-point was tumour resectability, Secondary end points included pathological tumour response and safety. Results: TACE attempted in 49 patients and was successful in 40. Reasons for failed TACE included arterial abnormality (n=2), progressive disease (n=2), bilobar disease (n=2), hepatoma (n=1), allergy to contrast (n=1) and concomitant infection (n=1). There was one post-TACE liver abscess (3%), and 1 post TACE pancreatitis (3%) (recognised complications). 38 patients have undergone hepatic resection so far, with R0 resection rate of 100% and no significant post-hepatectomy morbidity. Thirty day post-operative mortality was 7.6% (n=2), with neither death related to TACE (one intraoperative pneumomediastinum, one MODS after aspiration pneumonia). Complete pathological response (no viable tumour) was demonstrated in 15% of lesions, major response in 55% and minor response in 30%. Conclusion: Neoadjuvant DEBIRI TACE for resectable colorectal liver metastasis is safe and is not associated with increased post-hepatectomy morbidity. A single treatment with DEBIRI-TACE resulted in pathological response of tumour similar to that seen after systemic treatment, which may translate to improved progression free survival. Competing interests: None declared.